Profile of the Best World Logistics Practice - Jaroslav Kral (Communications, 2000)
The paper deals with an issue of supply chain management that is a trend in integrated logistics enterprise management. It gives a synthesised view on current logistics management practice of the best World companies. It defines reasons of supply chains genesis, conditions of an implementation and environment of operations improvements. Also it justifies an importance of information technologies, information systems and the Internet place here. The paper indicates the most important problem for solving is supply chain inventory to be minimised.